Methods for evaluating the benefits and harms of antenatal and newborn screening programmes adopted by health economic assessments: protocol for a systematic review - Nia Roberts; Stavros Petrou; Miaoqing Yang; May Ee Png (BMJ Open)
Introduction Complex organisational arrangements are required to deliver antenatal and newborn screening programmes. Decision-makers consider the benefits and harms of screening when reviewing the evidence about these programmes. Economic evaluations contribute one important part of this assessment process. However, it is not fully understood what approaches health economic assessments have adopted to measure and value benefits and harms. This study aims to systematically review and critique the published and grey literature on methods for identifying, measuring and valuing the benefits and harms of antenatal and newborn screening adopted by health economic assessments.Methods and analysis Nine bibliographic databases will be searched from 2000 onwards. These search strategies will be supplemented by manual reference searching of bibliographies, forward citation searching, contacts with experts, author searching and web searching for grey literature. Studies will be selected for review if they report health economic assessments of an antenatal or newborn screening programme. Assessments of title and abstracts and full reports will be undertaken independently with disagreements resolved through discussion. Data extraction will include fields to assess the reporting quality of the studies using the Consolidated Health Economic Evaluation Reporting Standards statement and a bespoke ancillary form to assess how benefits and harms have been accounted for.Ethics and dissemination This is an evidence synthesis review from already published materials and hence ethics committee approval or written informed consent will not be required. Our results will be disseminated by publishing in high-impact peer-review journals and presenting at relevant conferences.PROSPERO registration number CRD42020165236.